Suis, Na’sore, Nanuin: Kajian Antropologis-Teologis terhadap Siklus Kematian dalam Kebudayaan Amarasi - Fransina Lasi; Daud Saleh Luji; Lanny Koroh (Jurnal Teologi Kontekstual Indonesia, 2022)
The purpose of this research is to conduct a theological study of the culture of the Amarasi people in carrying out the death cycle rituals of suis, na'sore, nanuin in Soba Village. The research method used is qualitative-descriptive, using interview data collection techniques and documentation studies. The results of his research are anthropologically the ritual practices in the death cycle of suis, na'sore, nanuin aim to get rid of people who have died and provide safety protection for widows/widowers. However, theologically it turns out that there are practices that are irrelevant to the Christian faith because they deviate from Bible teachings, for example talking to people who have died and assuming that to get health and safety there are a number of taboos that must be done and this is the same as serving other gods in their case. are christians.